Estô dalam Komunitas Blater Madura: Perspektif Linguistik Digital dan Implikasinya terhadap Pendidikan Islam - Heni Listiana; Sri Nurhayati; Zilfania Qathrun Nada (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The traditional value system of estô, which emphasizes selfless service, solidarity, and respect within the blater Madura community, confronts challenges in its dissemination and adaptation in the digital era. This study aims to examine the influence of estô within the blater community, with a specific focus on the role of the kiai in guiding these values for Islamic communication and education. This study utilized a qualitative descriptive exploratory methodology, with data collected through interviews, participant observation, and document analysis. The findings indicate that digital linguistics plays a significant role in expanding religious understanding; however, challenges persist in maintaining conformity with correct Islamic principles. The value system of estô can be preserved in the digital era through appropriate adaptation, where technology has the potential to enrich religious education when balanced with the judicious oversight of the kiai. This research contributes to the development of technology-based Islamic education and provides recommendations for integrating digital platforms with Islamic principles in pedagogical contexts.